Quality characteristics of Huacaya alpaca fibre produced in the Peruvian Andean Plateau region of Huancavelica - Montes, M.=700 1 Quicaño, I.; Quispe, R.; Quispe, E.; Alfonso, L.
(Es, En)
Ilus., 15 ref.
Keywords: ALPACA; CALIDAD; FIBRAS DE ORIGEN ANIMAL; DIAMETRO; EDAD; SELECCION; SEXO; ESPAÑA